MoveONParkinson: developing a personalized motivational solution for Parkinson’s disease management - Alves, Beatriz; Mota, Pedro R.; Sineiro, Daniela; Carmo, Ricardo; Santos, Pedro; Macedo, Patrícia; Carreira, João Casaca; Madeira, Rui Neves; Dias, Sofia Balula; Pereira, Carla Mendes (Frontiers in Public Health, 2024)
Introduction Despite the effectiveness of exercise-based interventions on symptom management and disease progression, many people with Parkinson’s Disease (PwPD) do not exercise regularly. In line with the ubiquitous use of digital health technology, the MoveONParkinson digital solution was developed, comprising a Web Platform and a Mobile App with a Conversational Agent (CA). The interface features were designed based on the principles of Social Cognitive Theory with the goal of fostering behavior change in PwPD for sustained exercise participation and improved disease management. Methods Using a mixed methods approach, this study aimed to collect feedback, assess the acceptability of the Mobile App and the Web Platform, and evaluate the usability of the latter. Quantitative data, which included questionnaire responses and the System Usability Scale (SUS) scores, were analyzed using descriptive statistics, heatmaps, and correlation matrices. Qualitative data, comprising semi-structured and thinking-aloud interview transcripts, were subjected to an inductive thematic analysis. A total of 28 participants were involved in the study, comprising 20 physiotherapists (average age: 34.50 ± 10.4), and eight PwPD (average age: 65.75 ± 8.63; mean Hoehn & Yahr: 2.0 (± 0.76)). Results Three main themes emerged from the thematic analysis of the interviews, namely: Self-management (Theme 1), User Engagement (Theme 2), and Recommendations (Theme 3). The assessment of the Mobile App and the CA (mean score: 4.42/5.0 ± 0.79) suggests that PwPD were able to navigate this interface without notable difficulties. The mean SUS score of 79.50 (± 12.40%) with a 95% confidence interval ranging from 73.70 to 85.30, reveal good usability. Discussion These findings indicate a high level of acceptability of the MoveONParkinson digital solution, serving as a foundation for assessing its impact on exercise engagement and, subsequently, its influence on symptom management and quality of life of PwPD.